2024
DOI: 10.3389/fneur.2024.1329132
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for insomnia symptoms in hypertensive patients: a systematic review and meta-analysis

Jieying Zhang,
Xuancheng Zhou,
Hailun Jiang
et al.

Abstract: PurposeIn the realm of pain management, traditional Chinese medicine, specifically acupuncture, has garnered increasing attention. This meta-analysis pioneers the evaluation of acupuncture’s effectiveness in treating insomnia among hypertensive patients.MethodsWe conducted a comprehensive search across several databases—PubMed, Web of Science, Cochrane Library, WANFANG, China National Knowledge Infrastructure (CNKI), Sinomed, and the Chinese Journal of Science and Technology (VIP). Additionally, forward and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Before treating pain, traditional Chinese medicine such as acupuncture had been widely used to treat a wide range of ailments, and it has shown good results in different aspects. For example, within the realms of diabetes and neurological disorders, acupuncture exhibits remarkable advantages (33)(34)(35)(36). Network meta-analyses have previously explored traditional Chinese medicine interventions, including acupuncture (37).…”
Section: Discussionmentioning
confidence: 99%
“…Before treating pain, traditional Chinese medicine such as acupuncture had been widely used to treat a wide range of ailments, and it has shown good results in different aspects. For example, within the realms of diabetes and neurological disorders, acupuncture exhibits remarkable advantages (33)(34)(35)(36). Network meta-analyses have previously explored traditional Chinese medicine interventions, including acupuncture (37).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its unclear mechanism of action, the prevailing consensus suggests that acupuncture elicits systemic responses, particularly within the nervous system, through physical stimulation of specific points on the body's surface. This stimulation regulates bodily functions, ultimately yielding therapeutic effects (27,28). The publication of various controlled trials has demonstrated acupuncture's significant efficacy in managing pain syndromes, including acute and chronic low back pain, osteoarthritis of the knee, headaches, myofascial pain, neck pain, and fibromyalgia.…”
Section: Discussionmentioning
confidence: 99%